2018
DOI: 10.1128/aem.02134-17
|View full text |Cite
|
Sign up to set email alerts
|

Corrected and Republished from: Identification of Peptidoglycan Hydrolase Constructs with Synergistic Staphylolytic Activity in Cow's Milk

Abstract: Peptidoglycan hydrolases (PGHs) have been suggested as novel therapeutics for the treatment of bovine mastitis. However, activity in the presence of cow's milk is an important requirement for drugs administered into the bovine udder. We have used a microtiter plate-based protocol to screen a library of >170 recombinant PGHs, including engineered bacteriophage endolysins, for enzymes with activity against Staphylococcus aureus in milk. Eight suitable PGH constructs were identified by this approach, and their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
39
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 45 publications
2
39
0
1
Order By: Relevance
“…The observation that cocktail_2_TAT was also significantly more effective than were its individual components suggests that, besides CPP-mediated uptake, synergism also contributed to the potency of this enzyme mixture. Synergistic antibacterial effects when combining PGHs with different PG cleavage specificities have been reported previously (20) and may be explained by the increased accessibility of one PG cleavage site after cleavage of another (46). Here, we demonstrated that synergy can also be observed within intracellular compartments, following CPP-driven PGH uptake.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…The observation that cocktail_2_TAT was also significantly more effective than were its individual components suggests that, besides CPP-mediated uptake, synergism also contributed to the potency of this enzyme mixture. Synergistic antibacterial effects when combining PGHs with different PG cleavage specificities have been reported previously (20) and may be explained by the increased accessibility of one PG cleavage site after cleavage of another (46). Here, we demonstrated that synergy can also be observed within intracellular compartments, following CPP-driven PGH uptake.…”
Section: Discussionsupporting
confidence: 82%
“…Screening identifies PGHs with activity under extra-and intracellular conditions. To develop effective antimicrobials for the treatment of S. aureus infections involving intracellular and drug-resistant bacteria, we selected 322 PGH constructs with presumptive staphylolytic activity from an extensive library and assessed them in a microtiter plate-based screening assay (20) under conditions simulating relevant physiological settings. Each construct was rated based on its ability to eradicate or reduce S. aureus numbers under extracellular (phosphate-buffered saline [PBS] and Dulbecco's modified Eagle's medium [DMEM]), cytosolic (intracellular buffer), and lysosomal (lysosomal buffer) conditions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations